Multidrug-resistant Bacteria in Domestic Cats (Felis catus): A Global Health Threat Emerging from Pets - Mumtaza, Furzania; Jatmiko, Yoga Dwi; Salsabila, Maudy Syifa; Faturohmah, Yorda Nur; Fauziah, Ima; Saputra, Sugiyono (Graduate School, Universitas Brawijaya, 2026)
Cats (Felis catus) act as potential reservoirs for pathogenic bacteria due to their close contact with humans. Despite growing concerns about antimicrobial resistance (AMR) and zoonotic transmission, data on the diversity of antimicrobial-resistant bacteria, especially Staphylococcus aureus, in cats in Indonesia are limited. This study aimed to identify indicator bacteria in domestic cats and characterize their antimicrobial resistance (AMR) profiles. Nine earlobe swab samples were collected from cats at the Splendid Animal Market and Jalan Simpang Madukoro, Malang, in January 2023. White-toyellow colonies with hemolytic activity formed on blood agar. Six antibiotics are used to asses antimicrobial susceptibility. Based on the European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints, all isolates (100%) were resistant to rifampicin; seven isolates (78%) to oxacillin and cefoxitin; six isolates (67%) to gentamicin; four isolates (44%) to ceftriaxone; and one isolate (11%) to ciprofloxacin. Seven isolates (P1D, P3, P5, P7, R3, R5, and R9) were resistance to more than three antibiotic classes were classified as multidrug-resistant bacteria (MDR). Molecular identification using 16S rRNA gene sequencing and phylogenetic analysis revealed the isolates as Chryseobacterium sp. (P1D), Enterobacter hormaechei (P3), Acinetobacter sp. (P5), Enterobacter cloacae (P7), Exiguobacterium sp. (P9A), Staphylococcus sciuri (R1A), Enterococcus hirae (R3), Pantoea sp. (R5), and Stenotrophomonas maltophilia (R9). The detection of ceftriaxone resistance and the presence of MDR bacterial strains indicate that cats carry resistant bacteria that may impact public health.